A New Working Method in Psychiatric Care – The Impact of Implementation. Issue 3 (23rd February 2017) - Alverbratt, Catrin; Berlin, Johan; Åström, Sture; Kauffeldt, Anders; Carlström, Eric
ABSTRACT: An equal mix of organizational cultures is important for a successful implementation process. The aim of this study was to examine the implementation of a new working method in psychiatric hospital wards, representing different cultural characteristics. Descriptive quantitative data were collected at two hospitals (intervention and control). The results revealed one ward characterized by a mix of organizational cultures. This ward, compared with other intervention wards, showed the best results regarding patient assessed empowerment and participation. The result shows tentatively that organizational culture may have an impact on the implementation processes.